The e-Psychonauts’ ‘Spiced’ World; Assessment of the Synthetic Cannabinoids’ Information Available Online - Zangani, Caroline; Schifano, Fabrizio; Napoletano, Flavia; Arillotta, Davide; Gilgar, Liam; Guirguis, Amira; Corkery, John M.; Gambini, Orsola; Vento, Alessandro (Current Neuropharmacology, 2020)
Background: A wide range of novel psychoactive substances (NPS) is regularly searched and discussed online by web-based drug enthusiasts (i.e. the e-psychonauts). Among NPS, the range of synthetic cannabinoids (SC; ‘Spice’) currently represents a challenge for governments and clinicians. Methods: Using a web crawler (i.e. the NPS.Finder®), the present study aimed at assessing psychonauts’ fora/platforms to better understand the online mentions of SC. Results: The open-web crawling/navigating software identified here some 1,103 synthetic cannabinoids. Of these, 863 molecules were not listed in either the international or the European NPS databases. Conclusion: A web crawling approach helped here in identifying a large range of unknown SC likely to possess a misuse potential. Most of these novel/emerging molecules are still relatively unknown. This is a reason for concern; each of these analogues potentially presents different toxicodynamic profiles and there is a lack of docking, preclinical, and clinical observations. Strengthening multidisciplinary collaboration between clinicians and bioinformatics may prove useful in better assessing SC-associated public health risks.
Keywords: Psychonauts